Probabilities of Causation and Root Cause Analysis with Quasi-Markovian Models - Laurentino, Eduardo Rocha; Cozman, Fabio Gagliardi; Mauá, Denis Deratani; Lawand, Daniel Angelo Esteves; Coelho, Davi Goncalves Bezerra; Marques, Lucas Martins (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2025)
Probabilities of causation provide principled ways to assess causal relationships but face computational challenges due to partial identifiability and latent confounding. This paper introduces both algorithmic simplifications, significantly reducing the computational complexity of calculating tighter bounds for these probabilities, and a novel methodological framework for Root Cause Analysis that systematically employs these causal metrics to rank entire causal paths.